Coherent radiation recoil effect for the optical diffraction radiation beam size monitor at SLAC FFTB; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 227, iss. 1-2 - Potylitsyn A. P. Alexander Petrovich; Naumenko G. A. Gennadiy Andreevich; Aryshev A.; Fukui Y.; Cline D.; Zhou F.; Ross M.; Bolton P.; Urakawa J.; Muto T.; Tobiyama M.; Hamatsu R.; et al. (2005, 2005)
Title screen